ATTITUDE OF TEACHER EDUCATORS TOWARDS ICT - Ganesan, P.; Krishnakumar, R. (International Journal of Research -GRANTHAALAYAH, 2016)
Realizing the attitude of teacher educators towards ICT is essential to incorporate its betterments in teacher preparation programmes. This study examined the difference between teacher educators’ attitude towards ICT and their level of attitude; whether it is favourable or unfavourable? The participants were the teacher educators of Colleges of Education in Coimbatore, South India. Cluster Sampling was adopted. Results indicated significant difference in their attitude with respect to their locality of home. Majority of teacher educators have favourable attitude.